PENGARUH INSIDER OWNERSHIP DAN INSTITUTIONAL OWNERSHIP TERHADAP KINERJA PERUSAHAAN DENGAN COST OF EQUITY CAPITAL SEBAGAI VARIABEL MEDIASI - Arief Aqli Fahriza Nasution; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of ownership structure on the cost of equity capital and firm performance. Furthermore, it investigates whether the cost of equity capital serves as a mediating variable in the relationship between ownership structure and firm performance. The ownership structure is divided into insider ownership and institutional ownership. Firm performance is measured using return on equity (ROE), while the cost of equity capital is estimated using the Capital Asset Pricing Model (CAPM). The sample consists of 54 companies consistently listed in the KOMPAS100 index of the Indonesia Stock Exchange (IDX) during the 2021–2023 period, resulting in a total of 144 firm-year observations. The data were analyzed using panel data multiple regression with EViews 13. The results show that insider ownership has a significant negative effect on the cost of equity capital. Institutional ownership has a significant positive effect on firm performance. However, institutional ownership does not have a significant effect on the cost of equity capital, and neither insider ownership nor the cost of equity capital significantly affects firm performance. Consequently, the cost of equity capital does not mediate the relationship between both ownership structure and firm performance. These findings suggest that the cost of equity capital does not play a mediating role in the relationship between ownership structure and firm performance in the context of firms listed in the KOMPAS100 index.